FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CSR (CORPORATE SOCIAL RESPONSIBILITY) PADA PERBANKAN SYARIAH DI INDONESIA - Aviciena Zanjabil; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2015)
This study aims to examine the factors that affect the disclosure of CSR (Corporate Social Responsibility). Factors tested taken based on Islamic principles. Factors tested are IG - Score (Islamic Governance- Score) and IAH (Investment Account Holder). The population in this study is used throughout the Islamic banking in Indonesia. A total of 11 Islamic banking being the object of this study. Data collection method is study documentation using the annual report of each Islamic banking between 2011 to 2013. Regression analysis was used as a method of data analysis in research. The results showed that the variables of the IG - Score and the IAH has a significant association with the disclosure of CSR. In other words, the level of disclosure of CSR on Islamic banking is influenced by both factors.